2021
DOI: 10.1073/pnas.2005894118
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic LRRK2 regulates ciliation probability upstream of tau tubulin kinase 2 via Rab10 and RILPL1 proteins

Abstract: Mutations that activate LRRK2 protein kinase cause Parkinson's disease. We showed previously that Rab10 phosphorylation by LRRK2 enhances its binding to RILPL1, and together, these proteins block cilia formation in a variety of cell types, including patient derived iPS cells. We have used live-cell fluorescence microscopy to identify, more precisely, the effect of LRRK2 kinase activity on both the formation of cilia triggered by serum starvation and the loss of cilia seen upon serum readdition. LRRK2 activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 31 publications
6
48
1
Order By: Relevance
“…MLi-2 treatment showed an increase as reported [ 14 ], but the increase was very weak at ~1.1-fold ( Fig. 1A ), compared to the 2~3-fold increase previously reported in LRRK2 R1441C/G MEF cells [ 14 , 16 ].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…MLi-2 treatment showed an increase as reported [ 14 ], but the increase was very weak at ~1.1-fold ( Fig. 1A ), compared to the 2~3-fold increase previously reported in LRRK2 R1441C/G MEF cells [ 14 , 16 ].…”
Section: Resultssupporting
confidence: 71%
“…Further studies disclosed that PPM1H specifically dephosphorylated Rab proteins phosphorylated by LRRK2, and PPM1H knockdown suppressed ciliogenesis [ 15 ]. Sobu et al [ 16 ] reported that treatment of pathogenic LRRK2 R1441C MEF cells with MLi-2, an LRRK2 kinase inhibitor, significantly increased ciliogenesis at least 3-fold. Another study reported that the proportion of ciliated cells in HEK293T cells expressing LRRK2 pathogenic mutants Y1699C, G2019S, and R1441C, but not WT, was decreased and that MLi-2 treatment partially rescued ciliogenesis defects in the same cells expressing mutants only under serum-fed conditions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, like RILPL1, expression of HA-RILPL2 blocks ciliogenesis, perhaps by sequestering important components (such as MyoVa and/or Rab10) in a manner that interferes with their ability to function. Whereas RILPL1 overexpression blocks cilia formation by interfering with TTBK2 recruitment to the mother centriole (Sobu et al, 2021), RILPL2 overexpression blocks cilia formation by a different mechanism, as centriolar TTBK2 levels were not changed upon RILPL2 overexpression. It seems likely that in wild-type cells, RILPL2 overexpression interferes with MyoVa's ability to support early events in ciliogenesis that trigger CP110 uncapping independent of TTBK2.…”
Section: Discussionmentioning
confidence: 95%
“…Rab8a Q63L was cloned into a pET14b expression plasmid using Gibson assembly. mKO2-PACT was generated by amplifying the PACT domain of Pericentrin from cDNA of RPE cells as described (Sobu et al, 2021). To generate a plasmid-encoding Rab10 shRNA#1 and #2-resistant wild-type Rab10, inverse PCR was performed with primers (#1 F 59-ACTGCAAATATGGGATACAGCAGG-39, #1 R 59-TTAATCTTCTTTCCTTGTAATTCAACTG-39; #2 F 59-CACGGCATCAGG-TTTTTTGAGACTAG-39, R 59-TTCTCTAGCGATCTGTTCTCCTTTTCC-39) myc-Rab10 plasmid was used as a template, and the PCR product was self-ligated with T4 DNA ligase, and T4 polynucleotide kinase before transformation.…”
Section: General Cloning and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation